Evaluation of student internship programs to support the sustainability of vocational education institutions and industrial cooperation programs - Suhartanta Suhartanta; Ngatman Soewito; Hiryanto Hiryanto; Nunik Sugesti; Yosep Efendi; Siti Perdi Rahayu; Yusri Bin Kamin (Jurnal Pendidikan Vokasi, 2024)
The internship program is an annual routine activity in all faculties at Universitas Negeri Yogyakarta (UNY). This program implements a link and match between educational institutions and industry but has not been evaluated comprehensively. Therefore, conducting program evaluation research using the Context, Input, Process, and Product (CIPP) model is important. The type of research used is program evaluation research with the CIPP model. Data collection techniques in this research used questionnaires, interviews, and focus group discussions. The research subjects were UNY students who were grouped into four groups. Data were analyzed descriptively and quantitatively. The results showed that the context aspect of the internship program (goals and objectives) was in accordance with the graduate profile set at UNY. However, the general policy for organizing internships during the pandemic still needs to be developed. The systems and procedures of the academic community support the internship program, but there is still a need to improve cooperation documents and internship information systems for all faculties. The implementation of the internship program is in accordance with the activity plan set at UNY, but SIPKL needs to be developed to equalize the perception of field supervisors. The product of the internship program is in accordance with the goals and objectives set at UNY, but some students (34.16%) still have not received a job offer from the internship site. The results of this research can contribute to developing a quality-oriented internship program, which will then positively impact the cooperation relationship between universities and industry. Thus, a good working relationship will benefit both parties and potentially develop cooperation in other programs.